Sustainable Development Goals (SDGs) dan Pengentasan Kemiskinan Di Daerah Istimewa Yogyakarta - Nanda Bhayu Pratama; Eko Priyo Purnomo; Agustiyara Agustiyara (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
Entering the era of Sustainable Development Goals (SDGs), which is a continuation of the MDG's concept of poverty, remains an unresolved problem. Indonesia as a member of the United Nations is committed to tackling the problem of poverty along with the SDGs declaration. If seen poverty in Indonesia is a severe problem because it involves the issue of wide inequality. Various attempts were made by the central and regional governments to overcome the problem of poverty. Yogyakarta Province as one of the poorest provinces in Java has several goals and programs implemented to overcome poverty. These programs also involve several related agencies because poverty faced is a multidimensional poverty problem. These programs are contained in the RPJMD of the Special Province of Yogyakarta in the 2017-2022 period.